ANALISIS PRODUKSI TEH HITAM DI KEBUN TEH SINUMBRA SELAMA PADEMI COVID-19 - Pardian, Pandi; Esperanza, Dhany; Renaldi, Eddy; Budiman, Muhammad Arief; Sari, Medi Atikah; Aulia, Reza Melvina; Yubilanti, Laurensia Sri; Adzkia, Yamandita; Erlangga, Muhamad (Universitas Galuh, 2023)
One of the largest tea producers in Indonesia is the province of West Java, with a percentage of 69.59% of the total national production of 129 thousand tons in 2019 spread across various garden locations with different conditions. This is interesting to be studied, mainly related to the income from the production process of tea shoots in the tea garden of Sinumbra during the COVID-19 pandemic. This research uses a quantitative descriptive method by using data collection, interpretation, and analysis data to describe and explain the actual situation. The result shows that the average production cost of 14 types of tea is RP14,999 / kg. The type (grade) with the highest production results is the quality I type of Dust tea, while the type with the lowest production results is BOP tea 1 (a quality I). The largest income from the type of PF tea (Pekoe Fanning) is Rp. 5,423,673,094, with the biggest profit being the (quality I) type of BP tea (Broken Pekoe) of Rp. 24,499 / kg, and the biggest loss in (quality III) type of FLUFF tea is -Rp. 4,292 / kg.